The effect of sulphate on amount of pigments photosynthesis and activity of catalase,peroxidase and nitrate reductase in leaf and root of canola (Brassica napus L. cv Hyola 401) - Maryam Niakan; Mohammad hossain Mohammadi; Vali ollah Rameah; Abbas ali Nourinia (فیزیولوژی محیطی گیاهی, 2006)
In this research, the effect of different amounts of ammonium sulphate as sulphate fertilizer in 0, 50, 100, 150, 200 Kg/ha under farm conditions on amount of chlorophyll a, b, carotene and xanthophyll and enzymes activity of catalase, peroxidase and nitrate reductase were evaluated. The results showed that increasing of ammounium sulphate content were ncreased amount of chl a, b, carotene and xanthophyll in leaf of canola significantly. Peroxidase and nitrate reductase activities in root of treated plants increased with increasing of sulphate in soil, while the activity of catalase in two parts of canola (root and leaf) did not have any significantly changes at different contents of sulfur in soils.